Stem cell origin differently affects bone tissue engineering strategies - Mattioli-Belmonte, Monica; Teti, Gabriella; Salvatore, Viviana; Focaroli, Stefano; Orciani, Monia; Dicarlo, Manuela; Fini, Milena; Orsini, Giovanna; Di Primio, Roberto; Falconi, Mirella (Frontiers in Physiology, 2015)
Bone tissue engineering is a promising research area for the improvement of traditional bone grafting procedure drawbacks. Thanks to the capability of self-renewal and multi-lineage differentiation, stem cells are one of the major actors in tissue engineering approaches, and adult mesenchymal stem cells (MSCs) are considered to be appropriate for regenerative medicine strategies. Bone marrow MSCs (BM-MSCs) are the earliest- discovered and well-known stem cell population used in bone tissue engineering. However, several factors hamper BM-MSC clinical application and subsequently, new stem cell sources have been investigated for these purposes. The successful identification and combination of tissue engineering, scaffold, progenitor cells, and physiologic signalling molecules enabled the surgeon to design, recreate the missing tissue in its near natural form. On the basis of these considerations, we analysed the capability of two different scaffolds, planned for osteochondral tissue regeneration, to modulate differentiation of adult stem cells of dissimilar local sources (i.e. periodontal ligament, maxillary periosteum) as well as adipose-derived stem cells, in view of possible craniofacial tissue engineering strategies. We demonstrated that cells are differently committed toward the osteoblastic phenotype and therefore, considering their peculiar features, they may alternatively represent interesting cell sources in different stem cell-based bone/periodontal tissue regeneration approaches.